Avaliação das perturbações físicas de feixes de raios X em pequenos campos estáticos: uma abordagem teórica pelo método de Monte Carlo - Reginaldo Gonçalves Leão Júnior (2018)
The improvement of radiotherapy techniques has been conducted in order to prioritize the protection of healthy tissues, innovation in dosimetric conformation methodologies and the increase of its curative, ablative or analgesic ecacy. The most recent implementations have largely employed static elds with dimensions less than 4x4cm2 and dynamic elds. These congurations have fundamentally dierent specicities than those present in the conventional expositions, therefore, they required the creation of new dosimetric models. Its special features refer to the non-establishment of the idealized physical conditions in the traditional dosimetry protocols, and the localized charged particle disequilibrium. In view of this reality, was sought to contribute to the determination of correction factors that increase the agreement between the dierent dosimetry methods and instruments, and to improve the accuracy of the clinical planning of these techniques. Throughout the research, several computational simulations of static elds of X-ray beams collimated by stereotactic radiosurgery cones were performed, these simulations aiming to reproduce the exposures used in the clinical routine of Linear Accelerator calibration operating in photon mode with nominal energy of 6 MeV. The setup of the numerical dosimetry covered four dierent congurations: the exposure of a volume of water, using the DOSXYZnrc code, in addition to the exposure of three dierent specialized dosimeters, being a dosimeter diode, a single crystal diamond detector and a Pin Point ionization chamber. These last three are done using the egs_chamber code. The results showed the potential of the Monte Carlo Method for the reproduction of the dosimetric behavior of the modeled beams and for the quantication of the contribution of each of the disturbing factors in the nal dosimetric behavior. The inadequate dimensioning of the photon source at the linear accelerator head, proved to be a signicant source of disturbing errors of relative output factors measured in water. It was also noted that the level of collimation used to obtain the small elds causes such inuences on the lateral dose prole, which can result in inaccuracies in the lateral sizing of the beam of up to 10%. The modeling and simulation of specialized dosimeters, in a wide sampling of the most common clinical elds, allowed the determination of stopping power ratios and the perturbation factors of each of the components of the geometries of these instruments. These individualized factors have shown the causative agents of the total disturbance that a dosimeter causes in the local spectrum at a real exposure. Finally, the calculation and the use of the correction factors suggested in the unconventional eld dosimetry methodologies, promoted a better adjustment between doses measured by the dosimeters, with those quasi-punctual calculated directly in the water. This comparison revealed the potential of these techniques for increasing reliability and safety assurance in medical exposures employing small elds. These results are in addition to the worldwide eorts to quantify and improve the use of small elds, given the multiplicity of dosimetry instruments and collimation systems